Developing a social prescribing research school using translational research: Learning from Wales. (20th October 2021) - Wallace, C; Elliott, M
Abstract: The Wales School for Social Prescribing Research (WSSPR) was launched in April 2020. Central to its functioning, WSSPR uses a translational research model (Cooksey, 2007; Weeks et al 2013) to describe, order and organise a multi-phase programme of applied research, development and evaluation. It promotes an equal and mutually supporting relationship between theory-building, knowledge acquisition and practice, without privileging any one activity. Within WSSPR sits the Wales Social Prescribing Research Network. The network has a membership of over 300 individuals interested in social prescribing research across Wales, this includes academics, social prescribers, policy makers, health and social care professionals and commissioners. The school is also linked to three communities of practice in the North, West & Mid, and South East of Wales, which collectively reach over 1000 social prescribing practitioners. Through the translational research model, issues and questions are raised by practice or members of the public through the network to WSSPR. These inform thinking and development of research projects and proposals. The network is then used to disseminate findings, receive feedback on findings and implement evidence-based changes in practice. This presentation will discuss the development of WSSPR and our networks & communities of practice using a translational model of research to develop programmes of research for Wales. It will discuss the challenges and provide step by step developmental guidance about setting up a research organisation for SP. It will demonstrate the impact of the social prescribing research and its contribution to the evidence base to date.